Translocator Protein (TSPO) Expression in Platelets of Depressed Patients Decreases during Antidepressant Therapy - Sarubin, N.; Baghai, T. C.; Lima-Ojeda, J. M.; Melchner, D.; Hallof-Buestrich, H.; Wolf, L.; Hilbert, S.; Milenkovic, V. M.; Wetzel, C. H.; Rupprecht, R.; Nothdurfter, C. (Pharmacopsychiatry, 2016)
Introduction: A promising candidate in the field of pharmacological treatment options regarding major depressive disorder (MDD) is the mitochondrial translocator protein (18 kDa) (TSPO). TSPO is crucial for neurosteroid synthesis, which is in turn important for the regulation of emotions. It has already been shown that TSPO expression in platelets of depressed patients is reduced compared to healthy subjects.Methods: We measured TSPO levels in platelets of 37 depressed patients before and after 6 weeks of pharmacological treatment to test the hypotheses that i) such treatment would increase TSPO expression and ii) that this increase would be correlated with therapeutic response.Results: Surprisingly, TSPO levels in platelets of all patients were significantly reduced after 6 weeks of treatment (p=0.044). Within the responder group, a non-significant trend towards greater TSPO level reduction could be observed.Discussion: These results challenge our hypotheses that TSPO levels might increase during antidepressant therapy along with a decrease in depressive symptoms. Thus, we assume that TSPO expression in platelets is not a suitable state marker for MDD.
Keywords: TSPO; platelets; depression; antidepressant; therapy response